Understanding events from perception to action - Shipley, Thomas F.; Zacks, Jeffrey M.; Oxford eBooks (New York ; Oxford : Oxford University Press, 2008)
This book is the first to bring together computational neurological, and psychological research on how humans detect classify, remember, and act on events. It provides a comprehensive collection of research in these diverse fields.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Perception; Attention; Memory; Electronic books